2005
DOI: 10.1103/physreve.71.066408
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of optical conductivity of dense plasmas

Abstract: The optical conductivity sigma (omega) for dense Coulomb systems is investigated using molecular dynamics simulations on the basis of pseudopotentials to mimic quantum effects. Starting from linear response theory, the response in the long-wavelength limit k=0 can be expressed by different types of autocorrelation functions (ACF's) such as the current ACF, the force ACF, or the charge density ACF. Consistent simulation data for transverse as well as longitudinal ACF's are shown which are based on calculations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 35 publications
2
60
0
Order By: Relevance
“…In order to compare with the quantum statistical calculation, classical MD simulations have to be performed on the basis of a pseudo-potential which accounts for quantum effects at short interaction distances. A systematic analysis of MD simulations has been performed with respect to the dynamical structure factor [9] as well as the dc conductivity [1,10,11]. It was found that the analytical quantum statistical results are good approximations as long as Γ = e 2 /(4π 0 k B T )(4πn/3) 1/3 ≤ 1.…”
Section: Fully Ionized Plasmamentioning
confidence: 99%
“…In order to compare with the quantum statistical calculation, classical MD simulations have to be performed on the basis of a pseudo-potential which accounts for quantum effects at short interaction distances. A systematic analysis of MD simulations has been performed with respect to the dynamical structure factor [9] as well as the dc conductivity [1,10,11]. It was found that the analytical quantum statistical results are good approximations as long as Γ = e 2 /(4π 0 k B T )(4πn/3) 1/3 ≤ 1.…”
Section: Fully Ionized Plasmamentioning
confidence: 99%
“…which can be evaluated using quantum statistical approaches such as Green function theory, see [49], or numerical approaches such as MD simulations, see [50]. As collisions are relevant in strongly correlated systems, the dynamical collision frequency ν(ω) is derived and appears in a generalized Drude formula [51,52] …”
Section: Linear Response Theory Of Plasmas In Equilibriummentioning
confidence: 99%
“…Exemplarily, we refer to [50]. The state of a homogeneous one-component plasma in thermodynamic equilibrium is characterized by the nonideality parameter Γ = e 2 (4πn e /3) 1/3 (4πε 0 k B T e ) −1 and the degeneracy parameter Θ = 2m e k B T eh −2 (3π 2 n e ) −2/3 , T e is the temperature of the electrons.…”
Section: Linear Response Theory Of Plasmas In Equilibriummentioning
confidence: 99%
“…Further extension of the present mixed approach to more recent data for the model systems described by other effective potentials [5,25] is planned. Table I, but for Γ = 0.5, r s = 1.…”
Section: Discussionmentioning
confidence: 99%
“…(dashed) and quantal calculations (solid). In the classical case, the kinetic contribution is approximated by the Vlasov term (25), whereas in the quantal case expression (26) is used. …”
Section: Discussionmentioning
confidence: 99%